Molecular Symmetry - Willock, David J (West Sessex: Wiley, 2009)
Symmetry and group theory provide us with a formal method for the description of the geometry of objects by describing the patterns in their structure. In chemistry it is a powerful method that underlies many apparently disparate phenomena. Symmetry allows us to accurately describe the types of bonding that can occur between atoms or groups of atoms in molecules. It also governs the transitions that may occur between energy levels in molecular systems, which in turn allows us to predict the absorption properties of molecules and hence their spectra.
Appendices 299-414p.; Index 415-426p.
Keywords: Point group representations; Vibrational spectroscopy; Irreducible representations